Muslim Teachers Perspectives on Students Hedonism Behaviors - Makmur Makmur; Kamaruddin Kamaruddin; Yusra Yusra (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2021)
The aim of this study is to The aim of this paper is to discusse Muslim teachers perspectives on students hedonism behaviors at Senior High School Poso. This study used qualitative method in which the data was gathered through direct observation, in-depth interview with students’ parents, and written material. The results of the study concluded that many students has bad behavior such as consumptive, individualistic, selfish, lazy, irresponsible, wasteful, undisciplined in time, lying, disrespectful of time, shouting, likes to scold, likes to curse, and likes to fight. Besides that, students also like to annoy classmates, like to skip school, and disrespect teachers. The Islamic Religious Education teacher at the school views hedonistic behavior as behavior that can lead students to behavior that exceeds boundaries. Meanwhile, this behavior is very disliked by Allah and His Messenger, so that Islamic Religious Education teachers and stakeholders are expected to prevent hedonistic behavior among students so it does not damage their future.